Hypertension and quality of care in settlers in Angola - Malengue Satchama, Alfredo (2021)
Objective: To describe the characteristics of arterial hypertension and the quality of care received,in inhabitants of vulnerable villages in Angola. Methodology: Observational, descriptive and crosssectionalstudy in 113 representatives of families from the Candundu / São Pedro, Elumbi and Sanjimbivillages. The qualitative variables were exposed using absolute and relative percentage frequencytables; while for the quantitative variables means and standard deviation were used. Results:Regarding the measurement of HT, 38.9% presented blood pressure above normal ranges (SBP <130/ DBP <85), the patients presented symptoms such as dizziness or vertigo, headache and palpitations.Regarding the general perception of the living condition, 64.6% evaluated it as fair and 35.4% bad.Regarding the intervention, 100% expressed feeling satisfied with the assistance offered. Conclusion:Due to environmental conditions and the difficulty in accessing health services, among the familiesstudied there are many hypertensive patients, who see their disease aggravated by factors such asovercrowding, poor diet and poor living conditions.